MIM process of high-strength titanium alloy product and high-strength titanium alloy product
By modifying and optimizing the surface of titanium alloy powder and adding chloroacrylate oligomers to the binder, a new interaction mechanism between titanium alloy powder and binder was established, and the problem of poor compatibility between titanium alloy powder and binder in the existing MIM process was solved, and the strength and elongation of titanium alloy products were significantly improved.
Patent Information
- Application Number
- CN202510054901.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
In the existing MIM process, the compatibility and affinity of the titanium alloy powder and the binder are poor, resulting in phase separation during kneading, low strength of green body, poor pattern retention and dimensional stability. The titanium alloy products produced are generally low in strength and have poor elongation.
By modifying and optimizing the surface of titanium alloy powder, surface coating is used with branched polyethyleneimine, and adding chloroacrylate oligomers to the binder, a new interaction mechanism between the titanium alloy powder and the binder is established to improve compatibility and affinity.
The strength and elongation of the titanium alloy products prepared by the MIM process are significantly improved, the fluidity of the feed and the retention of the green body are improved, the density of the product is reduced, and the overall performance is improved.
Smart Images

Figure CN119839293A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of injection molding, and in particular to a MIM process for a high-strength titanium alloy product and the high-strength titanium alloy product. Background Art
[0002] As a high-quality light metal structural material and functional material, titanium alloy has the advantages of low density, high specific strength and specific fracture toughness, good fatigue strength and crack growth resistance, good biocompatibility, oxidation resistance, good low-temperature toughness, excellent corrosion resistance, non-magnetic, non-toxic, strong damping resistance, good heat resistance, good air absorption performance, etc. It has been widely used in aerospace, navigation, petroleum, chemical industry, metallurgy, automobile, power generation, biomedicine and other fields. However, due to its high melting point and hardness, difficult smelting and poor cutting performance, its cost has always been higher than other light metals.
[0003] Metal injection molding (MIM) is a new type of powder near-net forming technology formed by introducing injection molding technology into powder metallurgy. It is suitable for mass production of small and complex-shaped parts, and better solves the problem of high production cost of titanium alloy products.
[0004] The MIM process usually includes uniformly mixing metal powder and a binder, and obtaining alloy feed particles after granulation; the alloy feed particles are injected into the mold cavity by an injection molding machine in a heated and plasticized state to solidify and form a green body, and then the binder in the green body is removed by chemical or thermal decomposition methods, and finally the product is obtained by sintering and densification. In the above-mentioned MIM process, since the fluidity of the alloy feed has a direct impact on the product quality, the preparation of alloy feed with higher fluidity becomes a key link in MIM technology. However, in the existing MIM process, the compatibility and affinity between titanium alloy powder and binder are poor, which often leads to prominent problems such as phase separation during mixing, low green body strength, poor shape retention and dimensional stability. The strength of the manufactured titanium alloy products is generally low and the elongation is also poor. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a MIM process for high-strength titanium alloy products and high-strength titanium alloy products. By modifying and optimizing the titanium alloy powder and the binder, a new interaction mechanism between the titanium alloy powder and the binder is established, thereby improving the compatibility and affinity between the two, and improving the strength, elongation and other properties of the titanium alloy products prepared by the MIM process.
[0006] The present invention provides a MIM process for a high-strength titanium alloy product, comprising the following steps:
[0007] S1, mixing titanium alloy powder and a binder, extruding and granulating, and obtaining feed particles;
[0008] S2. After the feed particles are injection molded to obtain a green body, the green body is degreased and sintered to obtain the high-strength titanium alloy product.
[0009] Preferably, the titanium alloy powder is at least one of Ti-6Al-4V alloy powder, TA15 alloy powder or TC11 alloy powder;
[0010] Preferably, the titanium alloy powder is a gas atomized powder with a particle size of ≤150 μm, preferably 10-80 μm.
[0011] Preferably, the titanium alloy powder is surface-modified with branched polyethyleneimine so that the branched polyethyleneimine is adsorbed on its surface;
[0012] Preferably, the molecular weight of the branched polyethyleneimine is 500-10000.
[0013] In the present invention, the structural formula of branched polyethyleneimine is shown below. Since there are hydroxyl groups on the surface of titanium alloy powder and the surface of branched polyethyleneimine is rich in amino groups, hydrogen bonding can be achieved between the two, so that the branched polyethyleneimine is adsorbed on the surface of titanium alloy powder to form a coating.
[0014]
[0015] Preferably, the binder comprises, by mass percentage: 55-65% polyethylene glycol, 15-25% chlorine-containing acrylate oligomer, 5-10% polyoxymethylene, 5-10% polyethylene, 0.1-5% lubricant and 0.05-1% antioxidant;
[0016] Preferably, the chlorine-containing acrylate oligomer is formed by copolymerization of chloroethyl acrylate and methacrylate;
[0017] Preferably, the lubricant is paraffin and / or stearic acid, and the antioxidant is benzotriazole.
[0018] In the present invention, in addition to conventional polyethylene glycol, polyoxymethylene, polyethylene and other components, the binder also contains chlorine-containing acrylate oligomers. Since the chlorine-containing acrylate oligomers are formed by copolymerization of chloroethyl acrylate and methacrylate, the chloroethyl groups are contained in its molecular chain structure. For those skilled in the art, the chloroethyl groups can react with the tertiary amino groups on the branched polyethylene imine adsorbed on the surface of the titanium alloy powder to form quaternary ammonium ions, so the chlorine-containing acrylate oligomers in the binder can be coated on the surface of the titanium alloy powder by chemical reaction. On the one hand, the coating of the chlorine-containing acrylate oligomer greatly reduces the agglomeration effect between the titanium alloy powders, ensures that the feed particles have good fluidity, thereby achieving stable performance of the product; on the other hand, due to the chemical bonding mechanism formed between the titanium alloy powder and the binder, not only can the feed compatibility, green body performance and degreasing shape retention be improved, but also with the new interaction mechanism between the titanium alloy powder and the binder established between the two, the green body density and the strength and elongation of the titanium alloy product are also significantly improved compared with the past.
[0019] Preferably, the volume proportion of the binder is 20-40% of the total volume of the titanium alloy powder and the binder.
[0020] Preferably, before the titanium alloy powder is mixed with the binder, it is also premixed with boron-doped carbon nanotubes;
[0021] Preferably, the mass proportion of the boron-doped carbon nanotubes is 0.1-1% of the titanium alloy powder;
[0022] Preferably, the boron-doped carbon nanotubes are obtained by sintering a mixture of carbon nanotubes and boric acid.
[0023] In the present invention, titanium alloy powder and boron-doped carbon nanotubes are premixed. On the one hand, the boron-doped carbon nanotubes can effectively improve the thermal conductivity of the obtained titanium alloy product, thereby improving the heat transfer effect of the subsequent sintering of the titanium alloy powder, thereby improving the density of the obtained product, and then improving the strength; on the other hand, the interaction between the B element in the boron-doped carbon nanotubes and the Ti element in the titanium alloy powder can effectively link adjacent grains and exert a strengthening effect, thereby further improving the mechanical properties of the obtained titanium alloy product; in addition, it can be seen from the above analysis that since a chemical bond bonding method mainly based on quaternary ammonium groups is formed between the titanium alloy powder and the chlorinated acrylate oligomer in the binder, it presents a certain positive charge, which forms an electrostatic adsorption effect with the negatively charged boron-doped carbon nanotubes, which can not only weaken the effect of clustering between the boron-doped carbon nanotubes due to mutual attraction, but also further enhance the bonding effect between the boron-doped carbon nanotubes and the titanium alloy powder, ensuring the strengthening effect of the boron-doped carbon nanotubes on the titanium alloy product.
[0024] Preferably, the mixing temperature is 150-210°C and the time is 1-3h; the injection molding temperature is 160-220°C, the injection molding pressure is 70-130MPa, and the mold temperature is 80-120°C.
[0025] Preferably, the degreasing includes first acid degreasing and then thermal degreasing;
[0026] Preferably, the acid degreasing temperature is 90-130°C, the acid feeding amount is 1-2g / min, and the degreasing time is 4-8h; the thermal degreasing includes first heating to 200-300°C, keeping warm for 0.5-1h, and then heating to 500-600°C, keeping warm for 1-2h.
[0027] Preferably, the sintering comprises first heating to 750-850°C at a heating rate of 3-5°C / min, keeping the temperature for 1-3h, and then heating to 1200-1300°C at a heating rate of 1-3°C / min, and keeping the temperature for 1-3h.
[0028] The present invention also provides a high-strength titanium alloy product, which is prepared by the above-mentioned MIM process.
[0029] The present invention provides a MIM process for a high-strength titanium alloy product and a high-strength titanium alloy product, wherein titanium alloy powder and a binder are mixed and granulated to obtain a feed material, and then the feed material is injected into a mold cavity by injection molding to obtain a product green body; then the binder in the green body is removed by a degreasing process, and finally sintering and densification are used to obtain a titanium alloy product. The present invention can achieve excellent alloy feed fluidity and shape-maintaining ability by modifying the surface of titanium alloy powder and improving the formula of the binder, thereby preparing a titanium alloy product with good strength and elongation, and has the characteristics of simplicity, economy and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The figure is a flow chart of the MIM process for the high-strength titanium alloy product of the present invention. DETAILED DESCRIPTION
[0031] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0032] Example 1
[0033] This embodiment provides a MIM process for high-strength titanium alloy products, including:
[0034] (1) Ti-6Al-4V alloy powder (in terms of mass percentage, including Al 6.06%, V 4.22%, Fe 0.08%, C 0.01%, H 0.004%, O 0.12%, and the balance Ti) with an average particle size of 30 μm was added with branched polyethyleneimine (BPEI, M w =1800) in an aqueous solution and ultrasonically dispersed for 1 h, filtered, washed with water, and dried to obtain a titanium alloy powder with branched polyethyleneimine adsorbed on the surface;
[0035] (2) adding the titanium alloy powder with branched polyethyleneimine adsorbed on the surface and a binder in a volume ratio of 70:30 into an internal mixer, wherein the binder comprises, by mass percentage, polyethylene glycol (PEG, M w =10000) 60%, chlorine-containing acrylate oligomer 21%, polyoxymethylene (POM, 9520) 7%, polyethylene (HDPE) 8%, paraffin 1.8%, stearic acid 2%, benzotriazole 0.2%, after mixing at 180°C for 2h, adding into a twin-screw extruder for extrusion granulation to obtain feed granules;
[0036] The chlorine-containing acrylate oligomer is prepared by the following method: 2-chloroethyl acrylate, methyl methacrylate and azobisisobutyronitrile are added to acetone in a mass ratio of 1:2:0.05, stirred and reacted at 70° C. for 3 hours, and the acetone is removed by rotary evaporation to obtain the chlorine-containing acrylate oligomer;
[0037] (3) injecting the feed particles into a mold by an injection molding machine, heating the feed particles to a material temperature of 180° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 100° C. at a pressure of 100 MPa to obtain a green body;
[0038] (4) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 1.5 g / min. After acid degreasing at 110°C for 6 hours, the green body after acid degreasing is heated to 200°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept warm for 1 hour, and then heated to 550°C at a heating rate of 3°C / min, and kept warm for 1.5 hours. After degreasing, the green body is heated to 800°C at a heating rate of 4°C / min for pre-sintering for 2 hours, and then heated to 1250°C at a heating rate of 2°C / min for sintering for 2 hours, and then cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0039] Example 2
[0040] This embodiment provides a MIM process for high-strength titanium alloy products, including:
[0041] (1) adding TA15 alloy powder (in terms of mass percentage, comprising 6.56% Al, 2.21% V, 2.30% Zr, 0.06% Fe, 0.03% C, 0.004% H, 0.09% O, and the balance Ti) with an average particle size of 35 μm to a 1 g / L aqueous solution of branched polyethyleneimine (BPEI, Mw=1800) and ultrasonically dispersing for 1 h, filtering, washing with water, and drying to obtain a titanium alloy powder with branched polyethyleneimine adsorbed on the surface;
[0042] (2) adding the titanium alloy powder with branched polyethyleneimine adsorbed on the surface and a binder in a volume ratio of 80:20 into an internal mixer, wherein the binder comprises, by mass percentage, 65% of polyethylene glycol (PEG, Mw=10000), 15% of chlorine-containing acrylate oligomer, 10% of polyoxymethylene (POM, 9520), 5% of polyethylene (HDPE), 2.5% of paraffin wax, 2% of stearic acid, and 0.5% of benzotriazole; mixing at 150° C. for 3 h, adding the powder into a twin-screw extruder for extrusion granulation to obtain feed particles;
[0043] The chlorine-containing acrylate oligomer is prepared by referring to the method described in Example 1;
[0044] (3) injecting the feed particles into a mold by using an injection molding machine, heating the feed particles to a material temperature of 160° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 80° C. at a pressure of 130 MPa to obtain a green body;
[0045] (4) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 1 g / min. After acid degreasing at 90°C for 8 hours, the green body after acid degreasing is heated to 300°C at a heating rate of 5°C / min in a nitrogen atmosphere, and kept at this temperature for 0.5 hours. Then, the green body is heated to 500°C at a heating rate of 3°C / min and kept at this temperature for 2 hours. After degreasing, the green body is heated to 850°C at a heating rate of 3°C / min and pre-sintered for 1 hour. Then, the green body is heated to 1200°C at a heating rate of 3°C / min and sintered for 3 hours. Then, the green body is cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0046] Example 3
[0047] This embodiment provides a MIM process for high-strength titanium alloy products, including:
[0048] (1) Ti-6Al-4V alloy powder (in terms of mass percentage, including Al 6.06%, V 4.22%, Fe 0.08%, C 0.01%, H 0.004%, O 0.12%, and the balance Ti) with an average particle size of 30 μm was added with branched polyethyleneimine (BPEI, Mw =1800) in an aqueous solution and ultrasonically dispersed for 1 h, filtered, washed with water, and dried to obtain a titanium alloy powder with branched polyethyleneimine adsorbed on the surface;
[0049] (2) adding the titanium alloy powder with branched polyethyleneimine adsorbed on the surface and a binder in a volume ratio of 60:40 into an internal mixer, wherein the binder comprises, by mass percentage: polyethylene glycol (PEG, M w =10000) 55%, chlorine-containing acrylate oligomer 25%, polyoxymethylene (POM, 9520) 5%, polyethylene (HDPE) 10%, paraffin 2%, stearic acid 2%, benzotriazole 1%, after mixing at 210°C for 1h, adding into a twin-screw extruder for extrusion granulation to obtain feed granules;
[0050] The chlorine-containing acrylate oligomer is prepared by referring to the method described in Example 1;
[0051] (3) injecting the feed particles into a mold by an injection molding machine, heating the feed particles to a material temperature of 220° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 120° C. at a pressure of 70 MPa to obtain a green body;
[0052] (4) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 2 g / min. After acid degreasing at 130°C for 4 hours, the green body after acid degreasing is heated to 200°C at a heating rate of 5°C / min in a nitrogen atmosphere, and kept at this temperature for 1 hour. Then, the green body is heated to 600°C at a heating rate of 3°C / min and kept at this temperature for 1 hour. After degreasing, the green body is heated to 750°C at a heating rate of 5°C / min and pre-sintered for 3 hours. Then, the green body is heated to 1300°C at a heating rate of 1°C / min and sintered for 1 hour. Then, the green body is cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0053] Example 4
[0054] This embodiment provides a MIM process for high-strength titanium alloy products, including:
[0055] (1) A Ti-6Al-4V alloy powder (in terms of mass percentage, comprising 6.06% Al, 4.22% V, 0.08% Fe, 0.01% C, 0.004% H, 0.12% O, and the balance Ti) with an average particle size of 30 μm was added to a 1 g / L aqueous solution of branched polyethyleneimine (BPEI, Mw=1800) and ultrasonically dispersed for 1 h, filtered, washed with water, and dried to obtain a titanium alloy powder with branched polyethyleneimine adsorbed on the surface;
[0056] (2) adding the titanium alloy powder with branched polyethyleneimine adsorbed on the surface and the boron-doped carbon nanotubes in a mass ratio of 100:0.5 into a planetary ball mill and mixing them evenly, wherein the boron-doped carbon nanotubes are prepared by the following method: adding multi-walled carbon nanotubes with an average diameter of 50 nm into a boric acid solution with a concentration of 0.01 mol / L and ultrasonically dispersing them for 0.5 h, freeze-drying, heating them to 950° C. at a heating rate of 10° C. / min in a mixed atmosphere of H2 and Ar, pyrolyzing them for 2 h, and then cooling them to room temperature to obtain the boron-doped carbon nanotubes;
[0057] The obtained mixed powder and a binder are added into an internal mixer at a volume ratio of 70:30. The binder comprises, by mass percentage, 60% of polyethylene glycol (PEG, Mw=10000), 21% of chlorine-containing acrylate oligomer, 7% of polyoxymethylene (POM, 9520), 8% of polyethylene (HDPE), 1.8% of paraffin wax, 2% of stearic acid, and 0.2% of benzotriazole. After mixing at 180° C. for 2 hours, the mixed powder is added into a twin-screw extruder for extrusion granulation to obtain feed particles.
[0058] The chlorine-containing acrylate oligomer is prepared by referring to the method described in Example 1;
[0059] (3) injecting the feed particles into a mold by an injection molding machine, heating the feed particles to a material temperature of 180° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 100° C. at a pressure of 100 MPa to obtain a green body;
[0060] (4) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 1.5 g / min. After acid degreasing at 110°C for 6 hours, the green body after acid degreasing is heated to 200°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept warm for 1 hour, and then heated to 550°C at a heating rate of 3°C / min, and kept warm for 1.5 hours. After degreasing, the green body is heated to 800°C at a heating rate of 4°C / min for pre-sintering for 2 hours, and then heated to 1250°C at a heating rate of 2°C / min for sintering for 2 hours, and then cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0061] Comparative Example 1
[0062] This comparative example proposes a MIM process for a high-strength titanium alloy product, comprising:
[0063] (1) adding a Ti-6Al-4V alloy powder (in terms of mass percentage, comprising 6.06% Al, 4.22% V, 0.08% Fe, 0.01% C, 0.004% H, 0.12% O, and the balance Ti) having an average particle size of 30 μm and a binder in a volume ratio of 70:30 into an internal mixer, wherein the binder comprises, in terms of mass percentage, 60% polyethylene glycol (PEG, Mw=10000), 21% chlorine-containing acrylate oligomer, 7% polyoxymethylene (POM, 9520), 8% polyethylene (HDPE), 1.8% paraffin, 2% stearic acid, and 0.2% benzotriazole, and mixing at 180° C. for 2 h, adding the powder into a twin-screw extruder for extrusion granulation to obtain feed particles;
[0064] The chlorine-containing acrylate oligomer is prepared by referring to the method described in Example 1;
[0065] (2) injecting the feed particles into a mold by using an injection molding machine, heating the feed particles to a material temperature of 180° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 100° C. at a pressure of 100 MPa to obtain a green body;
[0066] (3) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 1.5 g / min. After acid degreasing at 110°C for 6 hours, the green body after acid degreasing is heated to 200°C at a heating rate of 5°C / min in a nitrogen atmosphere, and kept at this temperature for 1 hour. Then, the green body is heated to 550°C at a heating rate of 3°C / min and kept at this temperature for 1.5 hours. After degreasing is completed, the green body is heated to 800°C at a heating rate of 4°C / min and pre-sintered for 2 hours. Then, the green body is heated to 1250°C at a heating rate of 2°C / min and sintered for 2 hours. Then, the green body is cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0067] Comparative Example 2
[0068] This comparative example proposes a MIM process for a high-strength titanium alloy product, comprising:
[0069] (1) Ti-6Al-4V alloy powder (in terms of mass percentage, including Al 6.06%, V 4.22%, Fe 0.08%, C 0.01%, H 0.004%, O 0.12%, and the balance Ti) with an average particle size of 30 μm was added with branched polyethyleneimine (BPEI, M w =1800) aqueous solution, after ultrasonic dispersion for 1 h, filtering, washing with water, and drying to obtain a titanium alloy powder with branched polyethyleneimine adsorbed on the surface;
[0070] (2) adding the titanium alloy powder with branched polyethyleneimine adsorbed on the surface and a binder in a volume ratio of 70:30 into an internal mixer, wherein the binder comprises, by mass percentage, polyethylene glycol (PEG, M w =10000) 60%, acrylate oligomer 21%, polyoxymethylene (POM, 9520) 7%, polyethylene (HDPE) 8%, paraffin 1.8%, stearic acid 2%, benzotriazole 0.2%, after mixing at 180°C for 2h, adding into a twin-screw extruder for extrusion granulation to obtain feed granules;
[0071] The acrylate oligomer is prepared by the following method: methyl methacrylate and azobisisobutyronitrile are added to acetone in a mass ratio of 3:0.05, stirred at 70° C. for 3 h, and the acetone is removed by rotary evaporation to obtain the acrylate oligomer;
[0072] (3) injecting the feed particles into a mold by an injection molding machine, heating the feed particles to a material temperature of 180° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 100° C. at a pressure of 100 MPa to obtain a green body;
[0073] (4) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 1.5 g / min. After acid degreasing at 110°C for 6 hours, the green body after acid degreasing is heated to 200°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept warm for 1 hour, and then heated to 550°C at a heating rate of 3°C / min, and kept warm for 1.5 hours. After degreasing, the green body is heated to 800°C at a heating rate of 4°C / min for pre-sintering for 2 hours, and then heated to 1250°C at a heating rate of 2°C / min for sintering for 2 hours, and then cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0074] Comparative Example 3
[0075] This comparative example proposes a MIM process for a high-strength titanium alloy product, comprising:
[0076] (1) adding Ti-6Al-4V alloy powder (comprising 6.06% Al, 4.22% V, 0.08% Fe, 0.01% C, 0.004% H, 0.12% O, and the balance Ti) having an average particle size of 30 μm and boron-doped carbon nanotubes in a mass ratio of 100:0.5 into a planetary ball mill and mixing them uniformly to obtain a mixed powder;
[0077] The boron-doped carbon nanotubes are prepared by referring to the method described in Example 4;
[0078] (2) The mixed powder and the binder are added into an internal mixer at a volume ratio of 70:30. In terms of mass percentage, the binder includes: polyethylene glycol (PEG, M w =10000) 60%, chlorine-containing acrylate oligomer 21%, polyoxymethylene (POM, 9520) 7%, polyethylene (HDPE) 8%, paraffin 1.8%, stearic acid 2%, benzotriazole 0.2%, after mixing at 180°C for 2h, adding into a twin-screw extruder for extrusion granulation to obtain feed granules;
[0079] The chlorine-containing acrylate oligomer is prepared by referring to the method described in Example 1;
[0080] (3) injecting the feed particles into a mold by an injection molding machine, heating the feed particles to a material temperature of 180° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 100° C. at a pressure of 100 MPa to obtain a green body;
[0081] (4) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 1.5 g / min. After acid degreasing at 110°C for 6 hours, the green body after acid degreasing is heated to 200°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept warm for 1 hour, and then heated to 550°C at a heating rate of 3°C / min, and kept warm for 1.5 hours. After degreasing, the green body is heated to 800°C at a heating rate of 4°C / min for pre-sintering for 2 hours, and then heated to 1250°C at a heating rate of 2°C / min for sintering for 2 hours, and then cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0082] Comparative Example 4
[0083] This embodiment provides a MIM process for high-strength titanium alloy products, including:
[0084] (1) Ti-6Al-4V alloy powder (in terms of mass percentage, including Al 6.06%, V 4.22%, Fe 0.08%, C 0.01%, H 0.004%, O 0.12%, and the balance Ti) with an average particle size of 30 μm was added with branched polyethyleneimine (BPEI, M w =1800) in an aqueous solution and ultrasonically dispersed for 1 h, filtered, washed with water, and dried to obtain a titanium alloy powder with branched polyethyleneimine adsorbed on the surface;
[0085] (2) The titanium alloy powder with branched polyethyleneimine adsorbed on the surface and multi-walled carbon nanotubes with an average diameter of 50 nm were added to a planetary ball mill at a mass ratio of 100:0.5 and mixed evenly, and the resulting mixed powder and a binder were added to an internal mixer at a volume ratio of 70:30. In terms of mass percentage, the binder includes: polyethylene glycol (PEG, M w =10000) 60%, chlorine-containing acrylate oligomer 21%, polyoxymethylene (POM, 9520) 7%, polyethylene (HDPE) 8%, paraffin 1.8%, stearic acid 2%, benzotriazole 0.2%, after mixing at 180°C for 2h, adding into a twin-screw extruder for extrusion granulation to obtain feed granules;
[0086] The chlorine-containing acrylate oligomer is prepared by referring to the method described in Example 1;
[0087] (3) injecting the feed particles into a mold by an injection molding machine, heating the feed particles to a material temperature of 180° C. so that the feed particles have a certain fluidity, and injecting them into a mold cavity at a mold temperature of 100° C. at a pressure of 100 MPa to obtain a green body;
[0088] (4) The green body is added into a degreasing furnace, and oxalic acid is introduced at an acid feeding rate of 1.5 g / min. After acid degreasing at 110°C for 6 hours, the green body after acid degreasing is heated to 200°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept warm for 1 hour, and then heated to 550°C at a heating rate of 3°C / min, and kept warm for 1.5 hours. After degreasing, the green body is heated to 800°C at a heating rate of 4°C / min for pre-sintering for 2 hours, and then heated to 1250°C at a heating rate of 2°C / min for sintering for 2 hours, and then cooled to room temperature at a cooling rate of 10°C / min to obtain the high-strength titanium alloy product.
[0089] The tensile strength, yield strength and elongation of the high-strength titanium alloy products obtained in the above examples and comparative examples are measured according to GB / T 228.1-2010 standard; the density is measured according to GB / T1423-1996 standard to obtain the test results of density. The following Table 1 shows the properties of the high-strength titanium alloy products obtained in the above examples and comparative examples, as follows:
[0090] Table 1 Properties of high-strength titanium alloy products described in Examples and Comparative Examples
[0091] Performance Indicators Tensile strength / MPa Yield strength / MPa Elongation / % Density / % Example 1 1023 979 12.3 99.7 Example 2 1036 992 10.8 99.3 Example 3 1009 961 11.4 99.5 Example 4 1052 1009 12.1 99.8 Comparative Example 1 908 850 7.7 93.9 Comparative Example 2 936 884 8.1 95.5 Comparative Example 3 927 873 8.9 94.6 Comparative Example 4 1025 983 11.6 99.2
[0092] It can be seen from the above performance results that the properties such as strength and elongation of the high-strength titanium alloy product described in the embodiment have been effectively improved.
[0093] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A MIM process for high-strength titanium alloy products, characterized in that: The steps include: S1, mixing titanium alloy powder and a binder, extruding and granulating, and obtaining feed particles; S2. After the feed particles are injection molded to obtain a green body, the green body is degreased and sintered to obtain the high-strength titanium alloy product.
2. The MIM process of high-strength titanium alloy products according to claim 1, characterized in that: The titanium alloy powder is at least one of Ti-6Al-4V alloy powder, TA15 alloy powder or TC11 alloy powder; Preferably, the titanium alloy powder is a gas atomized powder with a particle size of ≤150 μm, preferably 10-80 μm.
3. The MIM process of the high-strength titanium alloy product according to claim 1 or 2, characterized in that: The titanium alloy powder is surface-modified by using branched polyethyleneimine so that the branched polyethyleneimine is adsorbed on its surface; Preferably, the molecular weight of the branched polyethyleneimine is 500-10000.
4. The MIM process of the high-strength titanium alloy product according to any one of claims 1 to 3, characterized in that: In terms of mass percentage, the binder comprises: 55-65% polyethylene glycol, 15-25% chlorine-containing acrylate oligomer, 5-10% polyoxymethylene, 5-10% polyethylene, 0.1-5% lubricant and 0.05-1% antioxidant; Preferably, the chlorine-containing acrylate oligomer is formed by copolymerization of chloroethyl acrylate and methacrylate; Preferably, the lubricant is paraffin and / or stearic acid, and the antioxidant is benzotriazole.
5. The MIM process of the high-strength titanium alloy product according to any one of claims 1 to 4, characterized in that: The volume proportion of the binder is 20-40% of the total volume of the titanium alloy powder and the binder.
6. The MIM process of the high-strength titanium alloy product according to any one of claims 1 to 5, characterized in that: Before the titanium alloy powder is mixed with the binder, it is also premixed with boron-doped carbon nanotubes; Preferably, the mass proportion of the boron-doped carbon nanotubes is 0.1-1% of the titanium alloy powder; Preferably, the boron-doped carbon nanotubes are obtained by sintering a mixture of carbon nanotubes and boric acid.
7. The MIM process of the high-strength titanium alloy product according to any one of claims 1 to 6, characterized in that: The mixing temperature is 150-210°C and the time is 1-3h; the injection molding temperature is 160-220°C, the injection molding pressure is 70-130MPa, and the mold temperature is 80-120°C.
8. The MIM process for high-strength titanium alloy products according to any one of claims 1 to 7, characterized in that: The degreasing includes first acid degreasing and then thermal degreasing; Preferably, the acid degreasing temperature is 90-130°C, the acid feeding amount is 1-2g / min, and the degreasing time is 4-8h; the thermal degreasing includes first heating to 200-300°C, keeping warm for 0.5-1h, and then heating to 500-600°C, keeping warm for 1-2h.
9. The MIM process for high-strength titanium alloy products according to any one of claims 1 to 8, characterized in that: The sintering comprises heating to 750-850° C. at a heating rate of 3-5° C. / min, keeping the temperature for 1-3 hours, and then heating to 1200-1300° C. at a heating rate of 1-3° C. / min, and keeping the temperature for 1-3 hours.
10. A high-strength titanium alloy product, characterized in that: It is prepared by the MIM process described in any one of claims 1 to 9.